Steady-State NTPase Activity of Dengue Virus NS3: Number of Catalytic Sites, Nucleotide Specificity and Activation by sRNA - Incicco, Juan Jeremías (2013)
Dengue virus nonstructural protein 3 (NS3) unwinds double stranded RNA driven by the free energy derived from the hydrolysis of nucleoside triphosphates. This paper presents the first systematic and quantitative characterization of the steady-state NTPase activity of DENV NS3 and their interaction with ssRNA. Substrate curves for ATP, GTP, CTP and UTP were obtained, and the specificity order for these nucleotides -evaluated as the ratio (kcat/KM)- was GTP=ATP=CTP > UTP, which showed that NS3 have poor ability to discriminate between different NTPs. Competition experiments between the four substrates indicated that all of them are hydrolyzed in one and the same catalytic site of the enzyme. The effect of ssRNA on the ATPase activity of NS3 was studied using poly(A) and poly(C). Both RNA molecules produced a 10 fold increase in the turnover rate constant (kcat) and a 100 fold decrease in the apparent affinity (KM) for ATP. When the ratio [RNA bases]/[NS3] was between 0 and *20 the ATPase activity was inhibited by increasing both poly(A) and poly(C). Using the theory of binding of large ligands (NS3) to a one-dimensional homogeneous lattice of infinite length (RNA) we tested the hypothesis that inhibition is the result of crowding of NS3 molecules along the RNA lattices. Finally, we discuss why this hypothesis is consistent with the idea that the ATPase catalytic cycle is tightly coupled to the movement of NS3 helicase along the RNA.